LEARNER FEEDBACK TO THE INITIAL TEACHER EDUCATOR’S EAP TEACHING: A REFLECTIVE STUDY - Ihtiara Fitrianingsih; Maman Suryaman; Jamilah Jamilah; Anwar Efendi (ELT Echo : The Journal of English Language Teaching in Foreign Language Context, 2022)
While the success of language instruction is unquestionably reflected in students’ performance in communicating in the target language, their voices generally can best express their success, disappointment, or complacency worth to reflect. This article, based on the study held at Universitas Negeri Yogyakarta in 2021, reports on a mixed-methods investigation that examines how an initial teacher educator (ITE) manages a course in English for academic purposes (EAP) from students’ perspectives. Fifty-five sociology education students selected through convenience sampling participated in a quantitative survey and focus group discussion. The quantitative data analysis shows students' positive views regarding the initial teacher educator's general performance, delivery, time management, material, media, assessment, and care. To complement the quantitative findings, the qualitative data scrutinized through thematic analysis suggest three imperative measures for more effective EAP instruction. Even though students rated ITEs performance as "Very Good" and her pedagogical competencies as "Very High," some qualitative data reveal the students' empirical voices that at least several adjustments must be made by acting on three imperative measures. This study provides insights into the self-study design for ITEs on upscaling their TPACK, professional commitments, and pedagogical identity.